Effect of Using Different Percentages of Sumac (Rhus Coriaria L.) On Broiler Performance - Rozhgar Baiz (University of Thi-Qar Journal of agricultural research, 2025)
This study is set to find out how broiler’s performance was affected by varying dosages of sumac extract. The birds were assigned to four treatments with three replicates, each 10 chicks. The first group was the control (ad libitum feeding) (T1), while the second group (T2) was 5gm Sumac/day, Third group (T3) was 10gm sumac, and fourth group (T4) was 15gm Sumac per day. The chick groups were allocated to 4 treatments with 3 replications, each 10 chicks. The results showed that there was no significant difference in weekly weight gain among the treatments. The second treatment (452.500 gm) gave the highest weight gain and not different significantly than  weight gain of these 3 treatments. In the period between 29-35 days, it was found that the chick of T4 gave the best feed convention Ratio. The third treatment (488.221) showed the best production index, while T1 showed the lowest production index. The fourth treatment (1.326) had the highest production index and had significant differences with T4 (232.240). Our findings demonstrate that incorporating Sumac into poultry diets has been shown to promote weight gain, thereby translating to superior production outcomes for poultry farmers.